Effect of Experimental Technology of Control in Physical Education of Students of Special Medical Groups with Respiratory Diseases on their Morphofunctional State - Корягін, В. М.; Блавт, О. З. (Physical Education Theory and Methodology, 2016)
The research objective is to analyze the dynamics of the parameters of the morphfunctional state of students of special medical groups with respiratory diseases under the influence of the experimental technology of control in physical education of students of these groups. Materials and Methods: pedagogical experiment, pedagogical testing: methods of recording of morphfunctional state parameters, functional tests and medical-biological tests, mathematical methods of digital data processing. Results. The paper presents the results of the experimental technology control tried and tested in physical education of the students of special medical groups with respiratory diseases. The foundation for the special analysis of the effectiveness of the effect the designed technology had on the morphfunctional state of the students of special medical groups with respiratory diseases is assessment of the monitoring results for its parameters during the period of implementation of the designed technology. The analysis of the data obtained confirms the statistic-significant changes (p < 0.05) by all the indicators under study in the students of experimental groups. Conclusions. The comparative characteristics of the functional indicators of the respiratory system of the students from the selection under study showed that the experimental groups had significantly better results than the reference groups (p < 0.05). This confirms the effective influence of the designed technology on the morphfunctional state of the students of the experimental groups.